2016
DOI: 10.1039/c6tc02186g
|View full text |Cite
|
Sign up to set email alerts
|

Tunable optical absorption in silicene molecules

Abstract: Two-dimensional materials with a tunable band gap that covers a wide range of the solar spectrum hold great promise for sunlight harvesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The only way to donate electrons without disturbing the out-of-plane π orbital is to modify the in-plane edges. A theoretical study of silicene molecules (large polycyclic molecules consisting of six-membered silicon rings) from Si 13 H 9 to Si 60 H 24 showed that silicene molecules with hydrogen atoms at the edge are not flat but have a low-buckled structure 30 . This indicates that, as described above, electron-donating substituents are good candidates for the formation of flat silicene molecules and hydrogen atoms are not suitable.…”
Section: Introductionmentioning
confidence: 99%
“…The only way to donate electrons without disturbing the out-of-plane π orbital is to modify the in-plane edges. A theoretical study of silicene molecules (large polycyclic molecules consisting of six-membered silicon rings) from Si 13 H 9 to Si 60 H 24 showed that silicene molecules with hydrogen atoms at the edge are not flat but have a low-buckled structure 30 . This indicates that, as described above, electron-donating substituents are good candidates for the formation of flat silicene molecules and hydrogen atoms are not suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Highly conjugated molecules are known to support plasmons by virtue of their free π‐electron cloud. Graphene and silicene have been shown to support strong molecular plasmons. Recently, the absorption profiles for silicene molecules were investigated using time‐dependent density functional theory (TD‐DFT) by Mokkath et al .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and silicene have been shown to support strong molecular plasmons. Recently, the absorption profiles for silicene molecules were investigated using time‐dependent density functional theory (TD‐DFT) by Mokkath et al . The plasmonic peaks in silicenes were inferred on the basis of a high oscillator strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly conjugated molecules are known to support plasmons by virtue of their free π-electron cloud. Graphene 9,10 and silicene 11 have been shown to support strong molecular plasmons. Quite recently, the absorption profiles for silicene molecules were investigated using time-dependent functional theory (TD-DFT) by Mokkath et al 11 The plasmonic peak in silicenes were inferred on the basis of a higher oscillator strength.…”
Section: Introductionmentioning
confidence: 99%